Strength analysis and optimisation of trailer agricultural machinery structures using finite element methods - V. Hruban; A. Drobitko; M. Khramov; M. Tovpyha (Machinery & Energetics, 2025)
The aim of the study was to examine the potential of numerical modelling for improving agricultural machinery by analysing its characteristics and technological features. A theoretical analysis was carried out using theoretical modelling, which allowed for the evaluation of stress-strain states of the machinery under different loads. It was found that numerical modelling reduced the weight of machinery by removing excess material in low-stress zones and also decreased emissions through improved geometry of working components, which contributed to energy savings and increased operational efficiency. It was revealed that modern technologies underestimated the potential of composite materials and nanotechnologies, which limited the achievement of higher strength, lightness, and durability indicators, while simplified models ignored variable climate factors, soil diversity, humidity, and temperature fluctuations, which affected wear and corrosion of the machinery. The study showed that agricultural machinery was subjected to dynamic, cyclic, vibrational, and impact loads, which caused fatigue failure of materials and local stresses, particularly in the areas of fastenings of working elements and hinged joints, which reduced service life and required improved materials. The results contributed to economic benefits for the agricultural sector through reduced fuel and maintenance costs, environmental sustainability through reduced emissions, and improved working conditions for operators by reducing vibrational loads. The results of the study could be used in the design and improvement of the structures of towed agricultural machinery, taking into account specific operating conditions, particularly for preliminary modelling and optimisation of the working elements of machines in agricultural regions with increased frame loads